Surgical outcomes of neoadjuvant chemoradiotherapy versus neoadjuvant chemotherapy in patients of locally advanced carcinoma of esophagus: A prospective cross-sectional comparative study - Jha, Rohit Kumar; Shalini Kumari,; Sumedha Gargy,; Rajen A Tankshali,; Kiran C Kothari, (Asian Journal of Medical Sciences, 2024)
Background: Neoadjuvant chemoradiotherapy + radiotherapy (NACT+RT) or neoadjuvant chemotherapy (NACT) has been shown to improve survival in locally advanced esophageal carcinoma (EC). Comparative evaluation of NACT+RT versus NACT is ambiguous. Aims and Objectives: The current study was designed to evaluate the outcomes of NACT+RT versus NACT in locally advanced EC. Materials and Methods: In this prospective cross-sectional study, patients with operable, non-metastatic squamous cell carcinoma, and adenocarcinoma of the mid and lower esophagus (T3–T4a) were treated with NACT (paclitaxel 175 mg/m2 plus carboplatin 5 Area under curve (AUC) every 3 weeks) or NACT+RT (NACT with 45 Gy in 25 fractions over 5 weeks). Response, R0 resections, post-operative complications, and recurrence were comparatively evaluated. Results: Of 40 enrolled patients, 20 received NACT and 20 received NACT+RT. In the NACT arm, 50% of patients had a partial response and 20% had disease progression. In the NACT+RT arm, 10% of patients had disease progression whereas 25% of patients had complete pathological response. Transhiatal esophagectomy was performed in 60% of patients in the NACT arm, whereas in the NACT+RT arm, 80% of patients had three-stage esophagectomy. The average surgery duration was numerically greater for the NACT+RT arm; blood loss was also greater. Pulmonary complications and anastomotic leak rate were higher in NACT+RT arm whereas other complications such as hoarseness of voice, and wound dehiscence were higher in the NACT arm. Conclusion: NACT+RT had better partial and complete response rates and low recurrence rates versus NACT. Post-operative complications were higher in the NACT+RT, especially pulmonary complications and anastomotic leak. Further, large-scale studies are warranted to confirm the efficacy of NACT versus NACT+RT in EC.